Mild therapeutic hypothermia after out-of-hospital cardiac arrest complicating ST-elevation myocardial infarction: Long-term results in clinical practice - Zimmermann, Stefan; Flachskampf, Frank A.; Schneider, Reinhard; Dechant, Katharina; Alff, Anna; Klinghammer, Lutz; Rittger, Harald; Achenbach, Stephan (Clinical Cardiology, 2013)
Background Recently, mild therapeutic hypothermia (MTH) has been integrated into the European resuscitation guidelines to improve outcomes after out-of-hospital cardiac arrest (OHCA). Data on long-term results are limited, especially in patients with acute ST-elevation myocardial infarction (STEMI). Hypothesis Invasive MTH influences long-term prognosis after OHCA due to STEMI. Methods We analyzed 48 patients who underwent emergency coronary angiography for STEMI after witnessed OHCA. In 24 consecutive patients, MTH was performed via intravascular cooling (CoolGard System, 34°C maintained for 24 hours) after initialization by rapid infusion of cold saline. Clinical, procedural, and mortality data were compared to 24 historical controls. Neurological recovery was assessed using the Cerebral Performance Category score (CPC) at 30-day and 1-year follow-up. Results Median time delay until arrival of emergency medical service was 6 minutes (MTH group) vs 6.5 minutes (controls) (P = 0.16). Initial rhythm was ventricular fibrillation in 75% vs 66.7% (P = 0.75). There were no differences regarding baseline characteristics, angiographic findings, and success of cardiac catheterization procedures. MTH was not associated with a higher frequency of bleeding complications or of pneumonia. Thirty-day mortality was 33.3% in both groups. One-year mortality was 37.5% (MTH group) vs 50% (controls) (P = 0.56). At 1 year, favorable neurological outcome (CPC ≤2) was significantly more frequent in the MTH group (58.3% vs 20.8%, P = 0.017). Multivariate analysis identified MTH as independent predictor of favorable neurological outcome (P < 0.02, odds ratio: 12.73). Conclusions MTH via intravascular cooling improves neurological long-term prognosis after OHCA due to STEMI and is safe in clinical practice. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-03-08

Out-of-hospital cardiac arrest and percutaneous coronary intervention for ST-elevation myocardial infarction: Long-term survival and neurological outcome - Zimmermann, Stefan; Flachskampf, Frank A.; Alff, Anna; Schneider, Reinhard; Dechant, Katharina; Klinghammer, Lutz; Stumpf, Christian; Zopf, Yurdagül; Loehr, Thomas; Brand, Georg; Ludwig, Josef; Daniel, Werner; et al. (International Journal of Cardiology, 2013)
Background: Predictors of long-term outcome after ST-elevation myocardial infarction (STEMI) complicated by out-of-hospital cardiac arrest (OHCA) are incompletely understood, including the influence of successful coronary reperfusion. Methods: We analysed clinical and procedural data as well as 1-year outcome of 72 consecutive patients who underwent primary coronary intervention (PCI) after witnessed OHCA and STEMI and compared the results with 695 patients with STEMI and PCI, but without OHCA. Neurological recovery after OHCA was assessed using the Cerebral Performance Category (CPC) scale. Results: PCI was successful in 83.3% after OHCA vs. 84.3% in the non-OHCA group (p = 0.87). One-year mortality was 34.7% vs. 9.5% (p < 0.001). 58.3% of the OHCA-patients showed complete neurological recovery (CPC 1) or moderate neurological disability (CPC 2). Another 6.9% showed severe cerebral disability (CPC 3) or permanent vegetative status (CPC 4). Delay from collapse until start of Advanced Cardiopulmonary Life Support (ACLS) was shorter for survivors with CPC status ≤ 2 (median 1 min, range 0-11 min) compared to non-survivors or survivors with CPC status > 2 (median 8 min, range 0-13 min), p < 0.0001. Age-adjusted multivariate analysis identified 'unsuccessful PCI', 'vasopressors on admission' and 'start of ACLS after > 6 min' as independent predictors of negative long-term outcome (death or CPC > 2). Conclusions: Mortality is high in patients with STEMI complicated by OHCA - even though PCI was performed with the same success rate as in patients without OHCA. The majority of survivors had favourable neurological outcomes at 1 year, especially if advanced life support had been started within ≤ 6 min and PCI was successful. © 2011 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac arrest; Outcome; Primary coronary intervention; Prognosis; Resuscitation; ST-elevation myocardial infarction